By any other name : a novel - Picoult, Jodi, 1966- (Ballantine Books, 2024)
"A captivating novel about two women, centuries apart, fighting to be heard - one of whom may be the real author of Shakespeare's plays - from the New York Times bestselling author of Wish You Were Here. As an undergraduate, Melina Green had a rare opportunity to have one of her first plays judged by famous theater critic Jasper Tolle, only to be publicly humiliated by a harsh and biased critique. Ten years later, her confidence as a playwright has never recovered, although she has just completed a work that she thinks is her best yet. It is based on the life of her ancestor Emilia Bassano, the first published female poet in England - and rumored to be the "Dark Lady" of Shakespeare's sonnets - but whom some scholars suspect may be the real author of a number of his plays. Melina wonders if she dares risk failure again, and then her best friend takes the decision out of her hands and submits it to a festival under a male pseudonym. In 1581, the young orphan Emilia Bassano is being raised in the ways of English aristocracy by the Baron Willoughby and his sister. Her lessons on languages, reading, and writing have endowed her with a sharp wit and a gift for storytelling. But like most women of her day, she has no control over her fate, and is ripped from her old life and forced to become a courtesan to Lord Hunsdon, a man knighted by Queen Elizabeth as the Lord Chamberlain in charge of all theater in London. Though she has no other freedoms, and inspired by the work of the most brilliant playwrights of the time, she pseudonymously sets her own pen to paper to tell a story. Told in dual intertwining timelines, this sweeping tale of ambition, courage, and desire centers two women who are determined to create something beautiful despite the prejudices they face. As Emilia alters the course of her life and therefore the course of the world, she blazes a trail. Centuries later, will Melina face the same terrible fate - to have her work celebrated, but only at the price of letting another take credit?"--